Clostridioides difficile infection and recurrence among 2622 solid organ transplant recipients. Issue 6 (11th October 2019) - Schluger, Aaron; Rosenblatt, Russell; Knotts, Rita; Verna, Elizabeth C.; Pereira, Marcus R.
Abstract: Background: Clostridioides difficile infection (CDI) is common after solid organ transplant (SOT) and is associated with high morbidity and mortality. Methods: We assessed incidence, risk factors, and outcomes of CDI among SOT patients at a large multi‐organ transplant center. Multivariable logistic regression was used to identify risk factors for initial and recurrent CDI. Results: A total of 2622 SOT patients were included. 224 (8.5%) had CDI 1 year post‐SOT. The highest incidence of CDI was among pancreas recipients (12.5%) followed by lung (11.7%), liver (11.0%), heart (10.8%), and kidney (5.8%). Median time to CDI was 56 days (range 2‐354) post‐SOT. About 64% of patients had severe CDI. About 56.3% were treated with metronidazole, 13.8% with oral vancomycin, and 28.6% with both. About 28.6% of patients had recurrent CDI. In multivariable modeling, lung transplant recipient status was the only significant predictor of recurrent CDI (OR 4.97, 95% CI 2.11‐11.78, P < .001) controlling for age, severe CDI, and pre‐SOT CDI. Post‐SOT CDI nearly doubled the risk of mortality at one year, in particular among those with severe CDI. Conclusions: In summary, CDI is highly prevalent, occurs early in the post‐transplant period, usually severe, with a high rate of recurrence, and associated with increased mortality within 1 year after transplant. The early post‐transplant period may be a crucial window to reduce CDI rates.